ANALISA PERTANGGUNGJAWABAN PIDANA BAGI DOKTER TERHADAP KASUS EUTHANASIA DITINJAU DARI KUHP YANG BERTENTANGAN DENGAN HAK ASASI MANUSIA - Tika Pramanasari, Dewa Ayu (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 04, Juni 2013, 2013)
Euthanasia poses a dilemma for the doctor because the doctor ending a patient's life when he will face legal consequences than it is contrary to human rights, namely the right to life, but also a patient man who has the right to determine the fate of what will happen in life, making it difficult for criminal liability for physicians when viewed from the Book of the Law - Criminal Code, the Criminal Code Article 304 doctors threatened to passive euthanasia Criminal Code and Article 344 of the Criminal Code for active euthanasia. So far euthanasia is an act which can not be applied because it is contrary to the Criminal Code. In this case the method used is based on the normative laws.
Keywords: Euthanasia, the Criminal Code, human rights